The Impact of Clay and Fluid Conductivity on the Electrical‐Diffusion Tortuosity Correlations in Sandstone Reservoirs - Mahmoud Elsayed; Ammar El‐Husseiny; Hyung Kwak; Abdulrauf R. Adebayo; Mohamed Mahmoud (Water Resources Research)
Abstract Tortuosity has different definitions that are used by scientists and engineers to describe various fluid‐related processes in porous media. Two of the most commonly used definitions are electrical (describing the electrical current flow process) and diffusion (related to the molecular diffusive flow process) tortuosity. In this study, we investigate the impact of minerology (presence of clay) and fluid conductivity on the electrical‐diffusion tortuosity relationship. That is: whether or not electrical and diffusion tortuosity have one‐to‐one relationship in sandstones. Two groups of samples were used: clean Fontainebleau sandstones and clayey sandstones. Electrical resistivity was measured using four‐electrode method to obtain electrical formation factor and calculate the electrical tortuosity (τe) using a model that is applicable for consolidated rocks. Pulsed field gradient nuclear magnetic resonance (PFG NMR) measurements were employed to quantify diffusion tortuosity (τD). At lower fluid conductivity (3 S/m), our results show that τD ≈τe for clean sandstones, while τe << τD is observed for clayey sandstones. We propose that mineralogy has direct impact on the τe−τD relationship: the presence of clay minerals added surface conductivity which contributed to underestimating the intrinsic formation factor (F′) and consequently reducing τe. As the fluid conductivity increases, τe converges to τD until reaching the high salinity limit at which F′ is obtained and τD becomes in good agreement with τe for the clayey sandstone. The NMR diffusion approach presented here shows the potential of estimating F′ without the need for multi‐salinity data which can contribute to improved permeability prediction.